Annahaashu - Berger, Melvin; Berger, Gilda (New York : Scholastic, 2006)
Presents an introduction to alligators and crocodiles for early readers, discussing their characteristics and behaviors, and looking at the differences between them.
Text in Arabic.
Translation of: Snap! : a book about alligators and crocodiles.
K-3
Keywords: Alligators; Crocodiles; Arabic language materials; Alligators; Crocodiles; Arabic language; Readers (Elementary)